Mobbing elektroniczny - analiza rozwiązań profilaktycznych i interwencyjncych - Pyżalski, Jacek; Knol, Kamila (Fundacja Dzieci Niczyje, 2011)
The paper analyzes preventive and interventional measures employed in the context of aggressive behaviors via mobile phones or Internet potentially occurring within peer groups. Cyberbullying is first characterized in terms of its origins, definitions and differences separating traditional bullying from bullying in cyberspace; as well as this, potential outcomes of this phenomenon are discussed. Part two of the article focuses on multiple preventive and interventional solutions implemented in this context in Poland and worldwide.
Keywords: cyberbullying; cyberbullying; profilaktyka; prevention; interwencja; intervention; edukacja; education